MODERN APPROACHES TO AUTOMATED BARRIER CONTROL: THE CASE OF THE HW-201 SENSOR (European Science Methodical Journal, 2024)
This article explores the development of an automated barrier control system using the HW-201 IR sensor. The project is based on the Arduino Nano microcontroller and a servo motor, with detailed descriptions of the system's technical specifications and operational principles. The system is designed to efficiently manage vehicle flow, enhance security, and reduce labor costs. Compliant with international standards such as ISO 12100 and IEC 61508, the solutions align with global automation practices. The simplicity of the software and the flexibility of the hardware components enhance the system's reliability.